Extensión de taxonomía y tratamiento de valores faltantes sobre un repositorio de incidentes de seguridad informática - Montealegre, Carlos Javier Carvajal; Bayona, Diego Nicolás; Ortiz Bayona, Zulima (Ingeniería, 2013)
This paper describes the missing-values estimation process through the Bayes theorem acting over an information security incident repository composed by categorical data. Additionally, an augmented taxonomy is defi ned to account for the identifi ed incidents.